25 need-to-know MBA models - Birkinshaw, Julian M.; Mark, Ken (Pearson, 2017)
25 Need-to-Know MBA Models provides easy access to the most useful models, tools and concepts that are covered on MBA programmes. Whether you are a student about to embark on an MBA or a manager who wants to understand the ideas taught, this guide will help you to get ahead.
Includes index. - Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Management; Gestion; management; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior